Evaluating the Relative Impact of Fiscal Incentives and Trade Policies on the Returns to Manufacturing in Taiwan 1955-1995 - Glenn P. Jenkins; Chun-Yan Kuo (Queen's University, Department of Economics, 2006)
In this paper, an integrated cash flow model is developed to examine the relative impact of tax incentives, financial subsidies, and macroeconomic variables on the profitability of industrial investments. It allows for various variables to interact with each other. An application of the model is carried out for Taiwan, which implemented a variety of fiscal incentives over the past forty years. The principal policy conclusion is that trade and macroeconomic policies are much more important than income tax incentives or subsidized finance policies in determining the success of industrialization process. The effects of any of the fiscal incentives are found generally much smaller than those of the trade policies or the fundamental trends in macroeconomic variables such as the movement of the real exchange rate and the real wage rate.
Keywords: H25; F13; O12; 330; tax incentives; export promotion; industrialization; real exchange rate; trade policy; Taiwan; Anreiz; Außenwirtschaftspolitik; Auslandsinvestition; Ausländisch; Industrie; Branchenentwicklung; Taiwan